PELAKSANAAN LAYANAN PENEMPATAN DAN PENYALURAN OLEH GURU PEMBIMBING DALAM KEGIATAN PEGEMBANGAN DIRI EKSTRAKURIKULER DI SMA NEGERI 12 PADANG - Susanti, Ratih; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
These  research     initiation and  background    by  implementation  service  on channel and placement with counselor in developing  selves  extracurricular action at  Senior High School  Negeri 12  Padang, these  research is  purposed  for  description  been doing by counselor at   Senior High School   Negeri 12 Padang. These  research   is purposed  for  seeing    how   is   assignment   service program  on channel and placement  extracurricular action  at  Senior  High School  Negeri  12 Padang, with   lay out research  that is  (1)  Assignment and planning   service program   on channel and placement by doing counselor extracurricular  action. (2)  Implementation   service program on channel and placement extracurricular action.  (3) Evaluation/Assessment. These research face off research qualitative, the research consist of all informant counselor at Senior High School Negeri 12 Padang.  The collecting data by doing   with   document and questioner upon   implementation   on channel and placement service by counselor extracurricular action. The  resulting   research  have  found  out  that is 1)  assignment and  planning   service  program   on channel and placement  extracurricular action  have   implemented  with  good category, 2) Implementation   service program  on channel and  placement  extracurricular act   have implemented   with good category, 3) Evaluation/assessment  of  implementation  service program  on channel and  placement  extracurricular act  into  good category.